A precise size-estimate for the small RNA products arising from Neurospora crassa Dicer activity - Paul ReFalo; Matthew S. Sachs (Fungal Genetics Reports, 2004)
Neurospora crassa cell-free extracts prepared from strains containing one or both functional Dicer genes, but not from a strain lacking functional Dicer genes, converts radiolabeled double-strand RNA (dsRNA) in an energy-dependent manner into short RNAs with an estimated size of 25-nt (Catalanotto et al. 2004). A smaller nucleolytic digestion product was also produced in an energy-dependent manner from either dsRNA or single-stranded RNA. Here we obtained more precise sizes for these products by electrophoresis of samples on a long (40-cm) denaturing DNA sequencing gel (20% polyacrylamide/7M urea).